HMGB1 Is a Potential Biomarker for Severe Viral Hemorrhagic Fevers. - Katarina Resman Rus; Luka Fajs; Miša Korva; Tatjana Avšič-Županc (Public Library of Science (PLoS), 2016)
Hemorrhagic fever with renal syndrome (HFRS) and Crimean-Congo hemorrhagic fever (CCHF) are common representatives of viral hemorrhagic fevers still often neglected in some parts of the world. Infection with Dobrava or Puumala virus (HFRS) and Crimean-Congo hemorrhagic fever virus (CCHFV) can result in a mild, nonspecific febrile illness or as a severe disease with hemorrhaging and high fatality rate. An important factor in optimizing survival rate in patients with VHF is instant recognition of the severe form of the disease for which significant biomarkers need to be elucidated. To determine the prognostic value of High Mobility Group Box 1 (HMGB1) as a biomarker for disease severity, we tested acute serum samples of patients with HFRS or CCHF. Our results showed that HMGB1 levels are increased in patients with CCHFV, DOBV or PUUV infection. Above that, concentration of HMGB1 is higher in patients with severe disease progression when compared to the mild clinical course of the disease. Our results indicate that HMGB1 could be a useful prognostic biomarker for disease severity in PUUV and CCHFV infection, where the difference between the mild and severe patients group was highly significant. Even in patients with severe DOBV infection concentrations of HMGB1 were 2.8-times higher than in the mild group, but the difference was not statistically significant. Our results indicated HMGB1 as a potential biomarker for severe hemorrhagic fevers.